The effect of private benefits of control on minority shareholders: A theoretical model and empirical evidence from state ownership - Kerry Liu (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2017)
Purpose: The purpose of this paper is to examine the effect of private benefits of control on minority shareholders. Design/methodology/approach: A theoretical model is established. The empirical analysis includes hand-collected data from a wide range of data sources. OLS and 2SLS regression analysis are applied with Huber- White standard errors. Findings: The theoretical model shows that, while private benefits are generally harmful to minority shareholders, the overall effect depends on the size of large shareholder ownership. The empirical evidence from government ownership is consistent with theoretical analysis. Research limitations/implications: The empirical evidence is based on a small number of hand-collected data sets of government ownership. Further studies can be expanded to other types of ownership, such as family ownership and financial institutional ownership Originality/value: This study is the first to theoretically analyse and empirically test the effect of private benefits. In general, this study significantly contributes to the understanding of the effect of large shareholder and corporate governance.
Keywords: G32; G34; 330; private benefits of control; minority shareholder; large shareholder; state ownership